Tissue factor prothrombotic activity is regulated by integrin-arf6 trafficking - Rothmeier, Andrea S. (Arterioscler Thromb Vasc Biol, 2017)
OBJECTIVE: Coagulation initiation by tissue factor (TF) is regulated by cellular inhibitors, cell surface availability of procoagulant phosphatidylserine (PS) and thiol-disulfide exchange. How these mechanisms contribute to keeping TF in a non-coagulant state and to generating prothrombotic TF remains incompletely understood. APPROACH AND RESULTS: Here we study activation of TF in primary macrophages by a combination of pharmacological, genetic and biochemical approaches. We demonstrate that primed macrophages effectively control TF cell surface activity by receptor internalization. Following cell injury, ATP signals through the purinergic receptor P2rx7 induce release of TF(+) microvesicles (MV). TF cell surface availability for release onto MV is regulated by the GTPase arf6 associated with integrin α4β1. Furthermore, MV proteome analysis identifies activation of Gα(i2) as a participating factor in the release of MV with prothrombotic activity in flowing blood. ATP not only prevents TF and PS internalization, but furthermore induces TF conversion to a conformation with high affinity for its ligand, FVIIa. Although inhibition of dynamin-dependent internalization also exposes outer membrane procoagulant PS, the resulting TF(+) MV distinctly lack protein disulfide isomerase and high affinity TF and fail to produce fibrin strands typical for MV generated by thrombo-inflammatory P2rx7 activation. CONCLUSIONS: These data show that procoagulant phospholipid exposure is not sufficient and that TF affinity maturation is required to generate prothrombotic MV from a variety of cell types. These findings are significant for understanding TF-initiated thrombosis and should be considered in designing functional MV-based diagnostic approaches.